Application of Mathematics in Physics and Chemistry in Secondary School - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2018)
In the frame of the project EFOP-3.6.1-16-2016-00022 „Debrecen Venture Catapult Program" a material was elaborated in which I summarize the most important applications of high school mathematics in physics and chemistry. It is important for the students to see that teaching mathematics is not self-serving but it can be applied in many problems in different natural sciences.